AB0717 Risk association between scleroderma disease characteristics, periodontitis and tooth loss. (12th June 2018) - Isola, G.; Williams, R.; Lo Gullo, A.; Matarese, M.; Ramaglia, L.; Matarese, G.
Abstract : Background: Systemic Sclerosis (SSc (is a multi-system disorder that can have significant adverse effects upon the health of the mouth. Objectives: The aim of this study was to investigate the associations between the disease characteristics of SSc, periodontal disease (PD) and tooth loss. Methods: Fifty-four patients affected by SSc and 55 non-diseased controls were matched for age and gender. SSc was characterised in subtypes and with the mean duration of disease and the Modified Rodnan Skin Score [mRSS]. Patients were surveyed and examined through the evaluation of the periodontal parameters and the number of teeth. Results: A logistic regression analysis showed that patients with SSc presented a higher number of missing teeth (p=0.001) and a significant median increased odds 2.95 (95% CI 1.26 to 6.84) of PD (defined as clinical attachment loss, CAL) compared to non-diseased controls (6.83, 95% CI 1.94 to 24.36). Moreover, the less values of PD was correlated with mRSS in the total SSc group and with the mean duration of disease in patients with limited SSc (p=0.007), even after adjusting this correlation with the presence of the major organs involvement. Conclusions: This study showed that patients with SSc presented an increased odds of PD and tooth loss compared to non-diseased controls. In SSc patients, the magnitude of PD was strongly associated with the mRSS and with the mean duration of the disease. The clinicians should be aware of the potential systemic health problems related to PD. References: [1] Matarese G, Isola G, Alibrandi A, et al. Occlusal and MRI characterizations in systemic sclerosis patients: A prospective study from Southern Italian cohort. Joint Bone Spine2016; 83: 57–62. [2] Matarese G, Isola G, Anastasi GP, et al. Immunohistochemical analysis of TGF-β1 and VEGF in gingival and periodontal tissues: a role of these biomarkers in the pathogenesis of scleroderma and periodontal disease. Int J ; Mol Med 2012 30: 502–8. Disclosure of Interest: None declared